Republic of Croatia : Staff Report for the 2000 Article IV Consultation and Request for Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2001)
Croatia achieved progress in restoring control over the public finances. Executive Directors welcomed the comprehensive economic program, with its focus on the fiscal deficit and tax reductions, wage discipline, and structural reforms in the context of a stable exchange rate. They stressed the need to maintain fiscal and monetary policies, and improve the economic statistics. They commended the country's banking system under a strengthened regulatory framework and improved supervision. They also appreciated Croatia's accession to the World Trade Organization.